The Usborne introduction to archaeology : Internet-linked - Wheatley, Abigail, 1974-; McNee, Ian; Reid, Struan; Woodcock, John (Tulsa, Okla. : EDC, 2004)
Provides an introduction to world archaeology, arranged by continent, and includes full-color photographs and illustrations, with information on what archaeology is, internet links for further research, a time line, glossary, and index.
First published: London : Usborne, 2004.
Includes index.
7.6
3-6
Keywords: Antiquities -- Juvenile literature; Archaeology -- Juvenile literature; Excavations (Archaeology) -- Juvenile literature; Antiquities; Archaeology; Excavations (Archaeology); Antiquities; Archaeology; Excavations (Archeology).